Association Between Landing Error Scoring System (LESS) Items and the Incidence Rate of Lower Extremity Stress Fracture. Issue 6 (9th June 2022) - Cameron, Kenneth L.; Peck, Karen Y.; Davi, Steven M.; Owens, COL(ret) Brett D.; Svoboda, COL(ret) Steven J.; DiStefano, Lindsay J.; Marshall, Stephen W.; de la Motte, Sarah J.; Beutler, COL(ret) Anthony I.; Padua, Darin A.
Background: Lower extremity stress fracture injuries are a major cause of morbidity in physically active populations. The ability to screen for modifiable risk factors associated with injury is critical in developing injury-prevention programs. Purpose: To determine if baseline Landing Error Scoring System (LESS) scores are associated with the incidence rate of lower extremity stress fracture. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 1772 participants with no history of lower extremity stress fracture were included. At preinjury baseline, the authors conducted a lower extremity movement assessment during a jump-landing task using the LESS. Incident lower extremity stress fractures were identified during a 4-year follow-up period. Potential incident cases were reviewed by 2 sports medicine fellowship–trained orthopaedic surgeons blinded to baseline LESS data. Univariate and multivariable Poisson regression models were used to estimate the association between baseline total LESS scores, individual LESS items, and the incidence rate ratio (IRR) of lower extremity stress fracture. Results: A total of 94 incident lower extremity stress fractures were documented, for a 5.3% (95% CI, 4.3%-6.5%) cumulative incidence. The overall LESS score was associated with the incidence rate of lower extremity stress fracture. For every additional movement error documented at baseline, there was a 15% increase in the incidence rate of lower extremity stress fracture (IRR, 1.15 [95% CI, 1.02-1.31]; P = .025). In univariate analyses, ankle flexion, stance width, asymmetrical landing, and trunk flexion at initial contact, in addition to overall impression, were associated with the incidence rate of stress fracture. After controlling for sex and year of entry into the study cohort, participants who consistently landed flat-footed or heel-to-toe were 2.33 times (95% CI, 1.36-3.97; P = .002) more likely to sustain a lower extremity stress fracture. Similarly, participants who consistently demonstrated asymmetric landing at initial contact were 2.53 times (95% CI, 1.34-4.74; P = .004) more likely to sustain a stress fracture. Conclusion: Components of the LESS may be associated with increased lower extremity stress fracture risk and may be helpful in efficiently assessing high-risk lower extremity biomechanics in large groups.